2018
DOI: 10.1002/pi.5580
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing antibacterial properties of polypropylene/Cu‐loaded montmorillonite nanocomposite filaments through sheath–core morphology

Abstract: Polypropylene (PP) loaded with copper-exchanged montmorillonite (Cu-MMT) nanocomposite filaments and films with excellent antimicrobial activity have been reported for the first time. A sheath-core morphology filament in which only the sheath contains Cu-MMT was prepared for maximizing bioactivity. Sodium MMT clay was modified to acid-activated MMT and further to Cu-MMT via an ion exchange process. The exchange operation was confirmed using wide-angle X-ray diffraction and energy-dispersive X-ray spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…34 Copper-loaded PA6/CuCNP microfibers were expected to exhibit excellent antibacterial activity in the inhibition zone test. 8,11 However, the results showed that the CuCNP-containing PA6 fabrics had no obvious inhibition zone against S. aureus and E. coli before or after being laundered 10 times (Figure 7). This can possibly be ascribed to the low copper content at the fiber surface and the low solubility and diffusion rate of CuCNPs.…”
Section: Resultsmentioning
confidence: 99%
“…34 Copper-loaded PA6/CuCNP microfibers were expected to exhibit excellent antibacterial activity in the inhibition zone test. 8,11 However, the results showed that the CuCNP-containing PA6 fabrics had no obvious inhibition zone against S. aureus and E. coli before or after being laundered 10 times (Figure 7). This can possibly be ascribed to the low copper content at the fiber surface and the low solubility and diffusion rate of CuCNPs.…”
Section: Resultsmentioning
confidence: 99%
“…, along with the concentrations of antibacterial agents. 14,15,21,44–48 Apparently, the copper nanoparticles and their antibacterial composites synthesized by the method described herein are characterized by low copper addition and high antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…5d depicts the antibacterial properties of PP-based antibacterial composites with various antibacterial agents, including metals, oxides, metals/oxides, etc., along with the concentrations of antibacterial agents. 14,15,21,[44][45][46][47][48] Apparently, the copper nanoparticles and their antibacterial composites synthesized by the method described herein are characterized by low copper addition and high antibacterial activity.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…[80][81][82] A lot of approaches have been performed to develop PP based polymeric materials having the antibacterial property. For example, inorganic particles including copper, 83 silver, [84][85][86] titanium oxide, 87 and zinc oxide 88 have been used as the antibacterial fillers although the deterioration of mechanical properties 84 and the elution of toxic particles 89 are known as the disadvantages. Since the antibacterial activity of CNC 90,91 and PDP [39][40][41] had been reported before, the antibacterial property of PP/CNC and/or PP/f-CNC was expected.…”
Section: Antibacterial Property Of Pp Nanocompositesmentioning
confidence: 99%